2021
DOI: 10.1111/jog.14873
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic fluid neutrophil gelatinase‐associated lipocalin and L‐type fatty acid‐binding protein in predicting fetal inflammatory response syndrome

Abstract: Aim To analyze the effectiveness of amniotic fluid neutrophil gelatinase‐associated lipocalin and L‐type fatty acid‐binding protein as predictive factors for fetal inflammatory response syndrome. Methods We classified single pregnancy cases into the fetal inflammatory response syndrome and nonfetal inflammatory response syndrome groups. We collected amniotic fluid at vaginal delivery and cesarean section and compared the patient characteristics, maternal white blood cell count, C‐reactive protein level, and am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“… [21] This study showed that the amniotic fluid NGAL level was strongly associated with intra-amniotic infection without being affected by other factors, and it was a useful predictor of FIRS, which is similar to the finding of a previous report. [4] There was also a higher NGAL level in the vaginally collection and blood contamination groups, and this may have been due to more inflammatory cells present in the cervix, vagina, and maternal blood.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“… [21] This study showed that the amniotic fluid NGAL level was strongly associated with intra-amniotic infection without being affected by other factors, and it was a useful predictor of FIRS, which is similar to the finding of a previous report. [4] There was also a higher NGAL level in the vaginally collection and blood contamination groups, and this may have been due to more inflammatory cells present in the cervix, vagina, and maternal blood.…”
Section: Discussionmentioning
confidence: 93%
“…Various amniotic fluid biomarkers have been reported, such as neutrophil elastase, lactate dehydrogenase, white blood cell, glucose, [1] interleukin-6, [2] and matrix metalloproteinase-9 levels, [3] for predicting intra-amniotic infection. We previously reported novel amniotic fluid biomarkers: the amniotic fluid neutrophil gelatinase-associated lipocalin (NGAL) level as a useful predictive factor of fetal inflammatory response syndrome (FIRS) [4] and L-type fatty acid-binding protein (L-FABP) as a useful predictive factor of fetal hypoxia. [5] Urinary NGAL and L-FABP levels are useful in detecting acute kidney injury caused by septic shock.…”
Section: Introductionmentioning
confidence: 99%
“…The additional members of this family (IL-27, IL-35, and IL-39) were identified more recently as being heterodimeric cytokines with a common subunit encoded by Epstein-Barr virus-induced gene 3 (EB13) [17]. Currently, elevated IL-6 is utilized as a biomarker for pregnancy dysfunction, and has been implicated or associated with chorioamnionitis [8,11,18,19], preeclampsia [20][21][22], and premature rupture of membranes [7,[23][24][25], and this elevation in IL-6 has been noted during placental disease in the horse [5,12,[26][27][28]. Little research has been done to assess IL-6 or its associated family members during healthy pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Reports indicate that IAI diagnosed in amniotic fluid specimens is associated with FIRS. [12][13][14][15] Of particular interest are cases with preterm premature rupture of membranes (PPROM), but IL-6 and tumor necrosis factor (TNF-α) were measured using amniotic fluid that accumulated in the vagina as a sample. A report showed that the diagnostic accuracy for FIRS and the area under the receiver operating characteristic curve (AUROC) were notably high at a maximum of 0.94 when IL-6 or TNF-α was combined with the findings of maternal inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…However, further studies are needed to clarify its diagnostic accuracy. Reports indicate that IAI diagnosed in amniotic fluid specimens is associated with FIRS 12–15 . Of particular interest are cases with preterm premature rupture of membranes (PPROM), but IL‐6 and tumor necrosis factor (TNF‐α) were measured using amniotic fluid that accumulated in the vagina as a sample.…”
Section: Introductionmentioning
confidence: 99%